The Effect of Service Quality, Promotion, and Customer Satisfaction on Wizzmie Purchase Decisions in Makassar City - Hasyim, Sitti Hajerah; Sri Utami (Cita konsultindo, 2025)
This study aims to analyze the influence of service quality, promotion, and customer satisfaction on purchasing decisions of Wizzmie consumers in Makassar City. Using a quantitative approach, data were collected through questionnaires from 100 respondents who had made purchases in the last three months. The analysis was conducted using the Structural Equation Modeling (SEM) method to determine the direct and indirect effects between variables. The results showed that service quality and promotion had a significant effect on customer satisfaction, which in turn influenced purchasing decisions. In addition, the three independent variables—service quality, promotion, and customer satisfaction—had a positive and significant effect on purchasing decisions. Customer satisfaction was the most dominant variable in influencing purchasing decisions. These findings provide strategic implications for Wizzmie managers in improving service quality and promotion effectiveness to encourage consumer loyalty and purchasing decisions.